Treatment of aggression in conduct disorders in children and adolescents - Karol Zagórski; Mateusz Kozik; Nina Skalska-Dziobek; Weronika Małagocka; Karolina Chybowska; Maria Naruszewicz; Przemysław Cetnarowski (Quality in Sport)
Introduction and purpose: Treatment of conduct disorders is complex, reflecting their combined etiology in organic developmental issues and improper environmental influences. Therefore therapy involves complex psychotherapeutic interventions, focusing not only on the individual, but also on his family system, and sometimes including drug treatment. The purpose of this work is to discuss the most effective treatment strategies for children with aggressive behavior.